BUILDING A NORDIC-LATIN AMERICAN COOPERATION AMONG HIGHER EDUCATION INSTITUTES IN FINLAND, DENMARK, AND BRAZIL - Cundari, Paula Casari; Freman, Mervi; Räikkönen, Marja; Pedersen, Jonna (Revista Conhecimento Online: Diversidade e Inclusão Social, 2018)
ABSTRACT Globalization puts pressure on the internationalization process of higher education. In this article, we describe the Beyond Alliance for Knowledge (BAK) strategic partnership process of three higher education institutions. The topic of the article is to analyse the creation process of the partnership from the viewpoints of the national higher education policies and institutional strategies. The promoting, prohibitive and crucial factors, as well as difficulties of the partnership process are reflected on theories. The data consists of the memos and reports of the partnership process in 2010-2017 and is analysed by qualitative content analysis. In BAK Alliance Feevale (Brazil), HAMK (Finland), and VIA (Danmark) are committed to increase collaboration in education, science, technology, and innovation to promote knowledge and regional, national, and international development. This is a great challenge considering multiple contexts, languages and cultures, but common interests and the conviction that innovative knowledge contribute towards transforming society, guide the goals and strengthens the partnership offering benefits for students, faculty and for the community of all three countries. Keywords: Higher education. Internationalization. Cooperation. RESUMO A globalização acelera o processo de internacionalização do ensino superior. Neste artigo, descrevemos o processo de parceria estratégica do Beyond Alliance for Knowledge (BAK) de três instituições de ensino superior. O propósito do artigo é analisar o processo de criação da parceria a partir dos pontos de vista das políticas nacionais de ensino superior e estratégias institucionais. Os fatores promotores, proibitivos e cruciais, bem como as dificuldades do processo de parceria, refletem-se na prática de construção da proposta. Os dados consistem dos memorandos e relatórios do processo de parceria em 2010-2017 e são analisados por meio de pesquisa qualitativa. No BAK Alliance, a Feevale (Brasil), a HAMK (Finlândia) e a VIA (Dinamarca) estão empenhadas em ampliar a colaboração em educação, ciência, tecnologia e inovação, para promover o conhecimento e o desenvolvimento regional, nacional e internacional. Este é um grande desafio considerando múltiplos contextos, idiomas e culturas; interesses comuns e a convicção de que o conhecimento inovador contribui para transformar a sociedade; orientar os objetivos e fortalecer a parceria, oferecendo benefícios para alunos, professores e para a comunidade dos três países. Palavras-chave: Educação superior. Internacionalização. Cooperação.